2020
DOI: 10.3389/fphar.2020.01059
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Heme Oxygenase 1/Carbon Monoxide Pathway to Resolve Lung Hyper-Inflammation and Restore a Regulated Immune Response in Cystic Fibrosis

Abstract: In individuals with cystic fibrosis (CF), lung hyper-inflammation starts early in life and is perpetuated by mucus obstruction and persistent bacterial infections. The continuous tissue damage and scarring caused by non-resolving inflammation leads to bronchiectasis and, ultimately, respiratory failure. Macrophages (MFs) are key regulators of immune response and host defense. We and others have shown that, in CF, MFs are hyper-inflammatory and exhibit reduced bactericidal activity. Thus, MFs contribute to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 222 publications
(333 reference statements)
0
16
0
Order By: Relevance
“…The effects of hyper-inflammation in inflammatory diseases are largely attributed to the impairment of several signaling pathways associated with cell responses toward oxidative stress, including the Nrf2/inducible heme oxygenase-1 (HO-1)/CO molecular axis [ 8 , 9 ]. Under oxidative stress, the HO-1 enzyme degrades heme group, leading to the production of potent antioxidant, anti-inflammatory, and bactericidal mediators (biliverdin, bilirubin, and CO) and monocytes/macrophages rely on abundant induction of the HO-1/CO pathway [ 10 ]. The overexpression of HO-1 during altered intracellular redox state confirms its role as an important component of stress response and suggests the cytoprotective effects exerted by CO, acting as gasotransmitter along with NO and H 2 S [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of hyper-inflammation in inflammatory diseases are largely attributed to the impairment of several signaling pathways associated with cell responses toward oxidative stress, including the Nrf2/inducible heme oxygenase-1 (HO-1)/CO molecular axis [ 8 , 9 ]. Under oxidative stress, the HO-1 enzyme degrades heme group, leading to the production of potent antioxidant, anti-inflammatory, and bactericidal mediators (biliverdin, bilirubin, and CO) and monocytes/macrophages rely on abundant induction of the HO-1/CO pathway [ 10 ]. The overexpression of HO-1 during altered intracellular redox state confirms its role as an important component of stress response and suggests the cytoprotective effects exerted by CO, acting as gasotransmitter along with NO and H 2 S [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the present results and other data (2) suggest that CO should be used with caution to treat lung inflammation. Based on its wide ranging beneficial effects, including dampening inflammation, reducing oxidative stress and strengthening host defense mechanisms [for review, see (14,43)], CO has been investigated as a therapy for lung inflammation in acute respiratory distress syndrome (16) and chronic obstructive pulmonary disease (COPD) (3). Like COPD (51), CF lung disease is characterized by persistent bacterial infection and exaggerated inflammatory responses (54).…”
Section: Previous Work Has Identified Two General Mechanisms Of Cftr Inhibition: Open-mentioning
confidence: 99%
“…HO-1 metabolites, including CO, are important in restoring redox homeostasis and resolution of inflammation, and it has been widely demonstrated that the HO-1/CO axis can help to prevent cellular and tissue damage. Therefore, the manipulation of the HO-1/CO system is an attractive strategy to treat conditions linked to oxidative-stress-induced inflammation, such as lung hyper-inflammation in cystic fibrosis, sepsis and modulation of chronic pain [ 2 , 3 , 4 , 5 , 6 , 7 ]. The chemistry of CO is unique: unlike NO and H 2 S that react indiscriminately with intracellular targets, CO offers the advantage of binding only to transition metals in a low oxidation state.…”
Section: Introductionmentioning
confidence: 99%